Efficacy of progesterone implants on induction of cyclicity in anestrous buffaloes - JEROME, A; SRIVASTAVA, S K; SHARMA, R K; PHULIA, S K (The Indian Journal of Animal Sciences, 2017)
The present study was designed to study if estrus induction response in anestrous buffaloes is augmented by priming using fabricated progesterone implants. For this study, progesterone implants with dose (150 mg and 350 mg) were fabricated with non-biodegradable, biocompatible polymer following standard protocol. These implants were tested as subcutaneous ear implants in 8 acyclic buffaloes for 7 days. Based on the estrus induction response and serum progesterone profile across days, 350 mg P4 implants were used for trial 2. In trial 2, three groups (8 each), viz. 1 [control: no treatment], 2 [progesterone depot 500 mg i.m. on day 0, progesterone s.c. ear implant (350 mg) on day 4, PMSG 500 IU on day 6 and P4 implant removal on day 7 followed by estrus detection and AI], 3 [progesterone depot 500 mg on day 0 i.m.; PMSG 500 IU i.m. on day 6 followed by estrus detection and AI ] were studied for estrus induction and fertility response. None (0.0%), 7 (87.5%) and 6 (75.0%) buffaloes were induced to estrus in groups 1, 2 and 3, respectively. Serum progesterone on day 7 was significantly higher in group 2 as compared to other groups. In group 2, four buffaloes ovulated out of which 3 conceived as compared to none in group 3. In summary, induction of estrus and ovulation in anestrous buffaloes by synergistic action of progesterone depot and implant ratify the potential scope of fabricated progesterone implants for inducing ovarian cyclicity in anestrous buffaloes.